STAKEHOLDER AND INSTITUTIONAL ANALYSIS IN THE MANAGEMENT OF LUBUK LARANGAN TEPIAN LAMO DUSUN RANTAU PANDAN BUNGO REGENCY JAMBI PROVINCE - Hertati, Rini (Asian Journal of Aquatic Sciences, 2022)
Lubuk larangan Tepian Lamo is located in Rantau Pandan Hamlet, Bungo Regency, Jambi Province. Formed in 2015 the formation was carried out in deliberation by the community, traditional leaders and the Livestock and Fishery Service of Bungo Regency, the management of Lubuk larangan was carried out based on the customary law of the local Hamlet. Monitoring of community participation is still relatively low, namely for thoughts 18.6%, property 15.5%, expertise 13.5% and personnel 20.3%. The high energy score is evidenced by the high participation of the community in carrying out mutual cooperation for opening, closing and mutual cooperation for repairing facilities and infrastructure in the Lubuk larangan area.